Psychological Features of Young People Involved with Social Latin Dancing - I A Novikova; D A Tolstova (Peoples' Friendship University of Russia (RUDN University), 2013)
The possibility of studying the personality by means of the psychological potential of the dance (salsa, for example) is discussed in the article. The results of the comparative empiric research of sociability, aggressiveness and conflict behavior styles in young people involved and not involved with social Latin American dances are presented and analyzed.